Reliability, discriminant validity and sex comparisons of dynamic postural stability during a landing task designed to challenge transverse plane knee stability - Sell, T. C.; Hufnagel, M.; Heebner, N.; Lephart, S. M. (Sports Biomechanics, 2021)
Internal and external rotational knee stability is essential for sports performance and excessive rotation can lead to injury but is rarely assessed in injury risk analysis. The objectives of this study were to determine the between-session reliability, discriminant validity and potential sex differences of a dynamic postural stability (DPS) assessment that challenges transverse plane knee stability. Thirty-six individuals (21.7 ± 2.6 years) including 19 females (20.8 ± 1.3 years) and 17 males (22.6 ± 3.4 years) participated. We measured DPS during rotational jump tasks (RJT) over 2 test sessions utilising a force plate. Kinematic (motion analysis) and electromyographic measures were compared to a traditional anterior-posterior jump task (APJT) to assess the discriminant validity and comparisons were performed between sexes. The intraclass correlation coefficients were between 0.67 and 0.86. Significant differences in transverse rotation angle at initial contact transverse rotational velocity of the knee were observed between the 2 different RJT and between the RJT and the traditional APJT. No sex differences were observed. The new assessment had good between-session reliability and offers a different challenge than a traditional jump task. This RJT may offer a novel assessment of knee joint rotational stability in conjunction with traditional measures.